The aerodynamic development of the new Porsche Cayenne. (February 2020) - Wolf, Thomas
With significantly enhanced performance, the third generation of the Porsche Cayenne is even more closely oriented towards the principles of sports cars. In addition to improving the driving-dynamic characteristics, the aim of the development was to lower the drag as a contribution towards the reduction of fuel consumption and emissions. Increasing performance and a simultaneous reduction of drag are conflicting objectives, which led to a number of aerodynamic challenges during the development of the new Cayenne. In addition to detailed aerodynamic optimisations, the solution for the new Cayenne consisted of an extended adaptive aerodynamic concept, which enables a compromise between fuel consumption, performance, and comfort depending on the driving condition. The first part of the concept comprises an extended air flap system that, for the first time, enables complete closing of all cooling air inlets in the front end. The second part of the concept is reserved for the top-of-the-range V8 Turbo model and consists of a multifunctional deployable roof spoiler that adapts to the aerodynamic characteristics of the relevant driving condition and features an air-brake function as a highlight.